Performance assessment method for crack repair in concrete using PZT-based electromechanical impedance technique. (June 2019) - Kim, Hyunjun; Liu, Xiaoming; Ahn, Eunjong; Shin, Myoungsu; Shin, Sung Woo; Sim, Sung-Han
Abstract: Concrete cracks are considered as an important indicator for potential damage and durability and are generally monitored in structural maintenance. A typical repair method in practice for concrete cracks involving with durability issues is to use alternative materials to fill the cracks. As the recovery quality of the repair is difficult to determine, an effective assessment approach is necessary. The electromechanical impedance (EMI) technique is a widely favored method; however, the determination of the frequency range and corresponding damage indicator is a governing factor for practical applications. Furthermore, its application to the evaluation of the crack repair performance has not been reported in the literature to date. This study presents an applicability of the PZT-based EMI technique for the quality assessment of crack repair in concrete. To determine an optimal frequency range that strongly reflects the structural condition, the trends of four damage indicators are investigated with multiple damage severities in each sub-frequency range. Subsequently, the performance of the crack repair material is evaluated using the predefined optimal frequency range with the damage indicators. The proposed approach is shown to effectively assess the recovery quality of the crack repair material over time.